Comparison of Rectal and Esophageal Sensitivity in Women With Functional Heartburn. (September 2016) - Freede, Margaret; Leasure, A. Renee; Proskin, Howard M.; Hatch, Daniel; Edwards, Karethy; Pascucci, MaryAnn; Smith, Patsy R.
Abstract : This study tested the primary hypothesis that there is a correlation of maximum pain threshold (MPT) in the esophagus and rectum in persons with functional heartburn. Secondary aims evaluated correlations with initial perception threshold (IPT) and pain threshold (PT). This study explored objective sensory endpoints of IPT, PT, and MPT in the esophagus and rectum of 14 females with functional heartburn to determine whether visceral hypersensitivity is generalized or organ-specific. Data on volume and pressure measurements at IPT, PT, and MPT with esophageal and rectal barostat distention were collected. The relationship of sensation and pain to volume, pressure, and compliance was analyzed. Esophageal and rectal IPT balloon volume scores were highly and significantly correlated ( r = .61, p = .02). Esophageal and rectal PT balloon volume scores were highly and significantly correlated ( r = .6, p = .02). Esophageal and rectal MPT balloon volume scores were not correlated ( r = .35, p = .26). The correlation of visceral sensitivity in the esophagus and rectum in persons with functional heartburn supports the hypothesis that visceral sensory changes in functional gastrointestinal disorders are not organ specific.